Helcococcus ovis Isolated from a Pulmonary Abscess in a Horse - Rothschild, Chantal M. (American Society for Microbiology, 2004)
Helcococcus ovis, a recently described organism cultured from sheep, was isolated in pure culture from a pulmonary abscess in a horse. This is the first report of this organism in horses and the first report in veterinary medicine to clearly demonstrate a pathogenic role for this organism.